Analyzing the runoff response to soil and water conservation measures in a tropical humid Ethiopian highland. (3rd September 2017) - Sultan, Dagnenet; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Adgo, Enyew; Tsubo, Mitsuru; Meshesha, Derege Tsegaye; Masunaga, Tsugiyuki; Aklog, Dagnachew; Ebabu, Kindiye
Abstract: Different soil and water conservation (SWC) practices have been implemented in many drought-prone parts of Ethiopia since the 1980s. We assessed the effect of SWC practices on runoff response and experimentally derived and tested the validity of the runoff curve number (CN) model parameter for the tropical humid highland climate of the Kasiry watershed in northwestern Ethiopia. We recorded daily rainfall and runoff depth from 18 runoff plots (30 m long × 6 m wide) representing the five main land-use types with various SWC practices and two slope classes (gentle and steep). CN values were derived using the lognormal geometric mean CN procedure. Runoff was significantly less from plots with SWC measures, with average reductions of 44 and 65% observed in cultivated and non-agricultural lands, respectively. Runoff on plots representing non-agricultural land was relatively accurately predicted with the derived CN method, but predictions were less accurate for plots treated with a SWC practice. We conclude that predicting the effect of SWC practices on runoff requires parameterization with separate sets of CN value for each SWC practice.